MAPAS NA WEB - Queiroz Filho, Alfredo Pereira de; Giannotti, Mariana Abrantes (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2012)
This work deals with the recent trends of maps on the Web. It is based on the finding that the maps have been shaped to the characteristics of network communications, that requires the integration and sharing of information. The combination of these two goals, in computational vocabulary, is called interoperability. This is based on two distinct processes: standardization and systematization. On the Web, the volume of maps produced increased exponentially and its functionalities amplified. However, part of the terms related to maps become ephemeral due to constant innovations arising from technological development. One of the main challenges is to make the content of maps universally comprehensible by humans and machines. The Spatial Data Infrastructures, collaborative maps, wide range of localization strategies, digital earth and cloud computing reveal important trends of development.